Psychical and demographic factors that influence trading on the stock exchange - Nikolett, Mihály; Imre , Madarász; Gabriella , Bánréti (Studia Mundi – Economica, 2018)
The need of self-care for the elderly has also appeared in Central and Eastern Europe in the changing political and economic conditions of today.The emerging responsibility of self-support directs attention to the opportunities provided by higher-yield investments, among others, the stock exchange. By avoiding the typical "investment mistakes" we can provide ourselves higher returns, living standards and a more relaxed age. In our study, we present the research results on the influences of the most important factors and a research with Hungarian university students, which focuses on the relationship between the demographic factors in the background and the stock exchange attitude.
Keywords: stock exchange; financial risk; risk attitude